Strategi Peningkatan Kinerja Mesin Bubut Berdasarkan Metode Overall Equipment Effectiveness Di PD XYZ - Sadam, Muhamad; Kurniawan, Dwi (e-Proceeding FTI, 2024)
Productivity is closely related to machine effectiveness, and optimal machine performance can increase the production output. PD XYZ's primary focus is on improving the efficiency of machine productivity. This research is motivated by the failure to achieve production targets and aims to propose improvement strategies based on the OEE method. The analysis results show that PD XYZ has a low OEE value of 50.74%. Performance efficiency remains the main factor contributing to the low OEE value. Consequently, this leads to high values of reduce speed losses and idle and minor stoppage losses, which are caused by the lack of repair capability, poorly organized tool storage, momentary machine stoppages, and materials not meeting specifications. Some improvement strategies that can be implemented include creating a schedule for raw material inspection, performing regular maintenance on the electrical components of the lathe machine, establishing an efficient SOP for the product manufacturing process sequence, and evaluating the expected ideal cycle time, which is hoped to enhance the effectiveness of the lathe machine used by PD XYZ. Keywords: Lathe Machine, Productivity, Efficiency, Preventive Maintenance. Produktivitas erat kaitannya dengan efektivitas mesin, kinerja mesin yang optimal dapat meningkatkan jumlah produksi. PD XYZ memiliki fokus utama dalam peningkatan produktivitas efisiensi mesin, penelitian ini dilatarbelakangi oleh tidak tercapainya target produksi dan bertujuan untuk mengusulkan strategi perbaikan berdasarkan metode OEE. Hasil analisis menunjukan bahwa PD XYZ memiliki nilai OEE yang rendah yaitu sebesar 50,74%. Performance efficiency masih menjadi faktor utama yang menjadi penyebab rendahnya nilai OEE. Oleh karena itu menyebabkan tingginya nilai reduce speed losses dan iddle and minor stoppage losses yang disebabkan oleh minimnya kemampuan perbaikan, cara penyimpanan alat yang tidak terorganisir dengan baik, mesin terhenti sesaat dan material yang tidak sesuai spesifikasi. Strategi perbaikan yang dapat dilakukan diantaranya membuat jadwal pemeriksaan raw material, melakukan perawatan komponen listrik mesin bubut secara berkala, membuat SOP urutan proses pengerjaan produk yang efisien dan melakukan evaluasi ideal cycle time yang diharapkan dapat meningkatkan efektivitas mesin bubut yang digunakan oleh PD XYZ. Kata kunci: Mesin Bubut, Produktivitas, Efisiensi, Pemeliharaan Preventif